6. Dziennikarstwo internetowe oraz media społecznościowe w Kirgistanie – znaczenie oraz społeczna odpowiedzialność .......... 271 - Oleszko-Pyka, Bartosz (Kirgistan – oblicza transformacji, 2020)
INTERNET JOURNALISM AND SOCIAL MEDIA IN KYRGYZSTAN – THE IMPORTANCE AND SOCIAL RESPONSIBILITYThe article presents the role of the media in Kyrgyzstan – a country which in the 21st century alone has witnessed a revolution and drastic political changes. The media has played and continues to play a key role in shaping Kyrgyz civil society. The dynamically changing situation of the mass media in Kyrgyzstan requires careful attention. Kyrgyzstan remains a litmus test of the political evolution of the entire region. For not only the political system of Kyrgyzstan depends on what role the media will play in the Kyrgyz Republic. The media situation will also affect the successful democratization of the media in neighbouring Central Asian countries.